2020
DOI: 10.1038/s41598-020-60407-6
|View full text |Cite
|
Sign up to set email alerts
|

Pleasant body odours, but not genetic similarity, influence trustworthiness in a modified trust game

Abstract: Identifying trustworthy partners is an important adaptive challenge for establishing mutually cooperative relationships. Previous studies have demonstrated a marked relationship between a person’s attractiveness and his apparent trustworthiness (beauty premium). Kin selection theory, however, suggests that cues to kinship enhance trustworthiness. Here we directly tested predictions of the beauty premium and kin selection theory by using body odours as cues to trustworthiness. Body odours reportedly portray inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The influence of body odors expands beyond attractiveness per se, following the "beautifulis-good stereotype" (Dion et al, 1972; see also the "halo effect"; Nisbett and Wilson, 1977), according to which desirable traits are attributed to individuals considered as beautiful. Translated to olfactory issues, exposure to pleasant body odors (male axillary sweat) induced trustworthiness attribution in a Trust Game (Lobmaier et al, 2020), whereby participants gave more money to a trustee during the game. Similar findings were reported in women following exposure to an isolated component of human body effluvium (i.e., hexanal;van Nieuwenburg et al, 2019).…”
Section: The Influence Of Body Odors On the Processing Of Invariant Face Characteristicsmentioning
confidence: 99%
“…The influence of body odors expands beyond attractiveness per se, following the "beautifulis-good stereotype" (Dion et al, 1972; see also the "halo effect"; Nisbett and Wilson, 1977), according to which desirable traits are attributed to individuals considered as beautiful. Translated to olfactory issues, exposure to pleasant body odors (male axillary sweat) induced trustworthiness attribution in a Trust Game (Lobmaier et al, 2020), whereby participants gave more money to a trustee during the game. Similar findings were reported in women following exposure to an isolated component of human body effluvium (i.e., hexanal;van Nieuwenburg et al, 2019).…”
Section: The Influence Of Body Odors On the Processing Of Invariant Face Characteristicsmentioning
confidence: 99%
“…Nevertheless, the many crossmodal effects of body odour and fragrance on multisensory person perception undoubtedly support earlier claims regarding the importance of scent to multisensory impression management (e.g., Baron, 1981 , 1983 ; Dabbs et al, 2001 ; Fiore, 1992 ; Higuchi et al, 2005 ; Kirk-Smith & Booth, 1987 ; König, 1972 ; Nezlek & Shean, 1995 ; cf. Lobmaier et al, 2020 ), while at the same time contradicting earlier claims that olfaction was irrelevant to social interaction (see Argyle, 1975 , pp. 227, 327).…”
Section: Discussionmentioning
confidence: 72%
“…Evaluating the evidence on fragrance effects on person perception, and the underlying cognitive mechanisms, where they are known, or have been suggested, may also help those wishing to critically evaluate the popular psychology literature that has developed around the suggestion that perfume can be used as an effective tactic of impression management in social and organizational settings (Baron, 1988 ; Levine & McBurney, 1986 ; Lobmaier et al, 2020 ; Newsweek, 1984 ; Zemke & Shoemaker, 2007 ), in non-verbal communication, and in order to engage in behavioural, or sensory, nudging (Baron, 1980 ; Cowley et al, 1977 ; De Lange et al, 2012 ; Ebster & Kirk-Smith, 2005 ; Gueguen, 2001 ; Gustavson et al, 1987 ; Hold & Schleidt, 1977 ; Hirsch, 1993 ; Hirsch & Gruss, 1999 ; Kirk-Smith & Booth, 1980 ; Liljenquist et al, 2010 ; Razran, 1940 ; Sczesny & Stahlberg, 2002 ; Taylor, 1968 , p. 53). 4 As might have been expected, and as we will see later, there has also been extensive commercial interest in supporting claims around the role of fragrance in attraction/attractiveness—i.e., both in terms of a fragrance’s ability to boost the wearer’s self-confidence, but also to influence how they are perceived by others (Berliner, 1994 ; Hirsch, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps unsurprisingly, interpersonal touch is rated as feeling more pleasant in the presence of a pleasant, as compared to an unpleasant ambient odour (Croy, D'Angelo, & Olausson, 2015; see Spence, 2020d for a review of the affective consequences of ambient scent/odour). Ambient scent also influences interpersonal trust (Lobmaier, Probst, Fischbacher, Wirthmüller, & Knoch, 2020 Here, one might also consider those sweet smells that have been shown to reduce pain, which can, perhaps be considered another kind of affective tactile sensation (or at least is often treated as such). For example, Prescott and Wilkie (2007) demonstrated that exposing their participants to a sweet pleasant scent resulted in being able to withstand the pain of the cold pressor test for significantly longer than if no scent or else a low sweetness scent was presented.…”
Section: Olfactory Contributions To Affective Touchmentioning
confidence: 99%